(untitled) (LACCEI, 2024)
The coastline of the city of Trujillo is is in constant dynamics and is reflected as erosion and accretion in its different beaches through the years. Therefore, the objective was to analyze the change in the line of the Coastal coastline of the city of Trujillo with GIS. were used Landsat TM, ETM+ and OLI TIRS satellite images during the period 1985 to 2022, the coastline was digitized with MNDWI and for the coastline analysis, the DSAS tool as well as NSM statistics (net movement) and EPR (exchange rate). As results, it was obtained that the district of Víctor Larco Herrera (playa Buenos Aires) had the greatest retreat of the coastline with - 129.07 m at a rate of -3.59 m/year, classifying it as an area with moderate erosion, on the other hand, in the district of Salaverry (El Frente and Salaverry North and South beaches) identified an increase in its coastline of 621.87 m with a rate of 17.20 m/year, classifying it as an area with very high accretion. It is concluded that hard constructions and natural phenomena such as the coastal El Niño Phenomenon have some influence with the modifications of the coast